El Excentrico, 1965-04-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
April 5, 1965 [5 de abril de 1965]. Ano 15, No 12. Cover is a campaign advertisement for John Castro and Ron Valdez, who were both running for city councilman seats numbers 1 and 2. The headline reads, "Vote Next Tuesday, April 13."